لغة الطفل في مسرحية الحافظة السوداء لغز الدين جلاوجي - معامير، أميمة, بوحامد، حنان (University of El-oued, 2022)
تهدف هذي الدراسة الى الكشف عن مدى أثر المسرح على لغة الطفل وقد اتخذنا من مسرحية الحافظة السوداء لعز الدين جلاوجي، حيث من خلال ما تم دراسته، توصلنا إلى الأهمية والدور الذي يلعبه المسرح في بناء لغة الطفل This study aims to reveal the extent of the impact of theater on the child's language We have taken from the play Al-Hafza Al-Black by Izz Al-Din Jalawji, where through what has been studied, We reached the importance and the role that theater plays in building a child's language. key words
Keywords: المسرح- لغة الطفل- مسرحية الحافظة السوداء; Theatre, the language of the child, the play of the black clipboard